2020
DOI: 10.5296/ijhrs.v10i1.16043
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the Social Media Process: The Impact of Internet Celebrity Word-of-Mouth Communication and Relationship Quality on Consumer Information Sharing

Abstract: With the rapid development of "Internet plus", the number of Internet users in China has increased rapidly, and the number of active users of social media software ranks first in the world. Large Numbers of network users are also potential consumer groups. Social media influences other consumers through consumer interaction and social interaction, and consumers are transformed into active information acquisition rather than passive information reception. Word of mouth marketing on social media has become one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…In the field of consumer behavior research, it is found that individuals with high self-enhancement motives conduct word-of-mouth communication and other behaviors based on the need of impression decoration so as to form a good impression in the hearts of others (Chu et al. , 2019; Liu and Fang, 2020). Impression management theory supports the relationship between self-enhancement motivation and word-of-mouth communication behavior.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…In the field of consumer behavior research, it is found that individuals with high self-enhancement motives conduct word-of-mouth communication and other behaviors based on the need of impression decoration so as to form a good impression in the hearts of others (Chu et al. , 2019; Liu and Fang, 2020). Impression management theory supports the relationship between self-enhancement motivation and word-of-mouth communication behavior.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…In (Yu & Jin, 2020), the necessity and components of modelling the marketing influence on the purchasing behaviour of a fast-growing segment of users of online stores are substantiated. The article (Liping & Chih, 2020) qualitatively describes Internet users as potential consumers, their interaction in social networks, and their mutual influence. Oral Internet communication, the quality of relationships, and information exchange are considered in detail.…”
Section: Introductionmentioning
confidence: 99%